ANALYSIS OF PATIENT CHARACTERISTICS AND DRUG UTILIZATION IN BIPOLAR DISORDER AT DR. SARDJITO GENERAL HOSPITAL - YOGYAKARTA - Wirasto, Ronny Tri; Swastika Dewi; Windhy Monica; Soewadi (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2026)
Introduction: Bipolar disorder is a chronic psychiatric disorder characterized by alternating episodes of mania/hypomania and depression. These episodes significantly compromise patients’ quality of life. Understanding patients’ sociodemographic characteristics, clinical profile, and drug utilization patterns is critical for ensuring therapy effectiveness and preventing relapse. This study aims to analyze characteristics of patients with bipolar disorder, relationships between sociodemographic factors and types of mood episodes, as well as drug utilization patterns among inpatients at Dr. Sardjito General Hospital, Yogyakarta. Methods: Data from 72 inpatients diagnosed with bipolar disorder according to ICD-10 (codes F31.0–F31.7) and admitted between January 2021 and December 2023 were included in this analytical cross-sectional study. Data were extracted from patients’ electronic medical records and analyzed using the Fisher-Freeman-Halton test. Results: A total of 52.8% patients were diagnosed with severe depressive episode with psychotic symptoms (F31.5), thereby making it the top diagnosis. Results also demonstrate a correlation between types of mood episodes and all sociodemographic characteristics of respondents, including age (p=0.011), sex (p=0.029), marital status (p=0.025), educational background (p=0.030), and occupation (p=0.017). Quetiapine was the most used antipsychotic drug (56.8%), whereas Fluoxetine was the most common antidepressant (64.9%). Diazepam (42.2%) and Divalproex (74.3%) were the most frequently prescribed sedative and mood stabilizer, respectively. Discuss: Frequent use of antidepressants, particularly fluoxetine, in patients with bipolar disorder. Because antidepressants cannot be used as monotherapy in bipolar disorder due to the risk of switching into mania or rapid cycling, their presence in the medication profile should be interpreted as adjunctive therapy within combination regimens rather than stand-alone treatment. Conclusion: Sociodemographic characteristics of patients are associated with types of mood episodes associated with bipolar disorder. These findings highlight the need for personalized therapies that take patient characteristics into account to improve the effectiveness of bipolar treatment. Keywords: bipolar, characteristic, treatment.